Massive transfers of resources - George C. Abbott (Intereconomics, 1983)
What lies behind the call for massive transfers of resources from the rich to the poor countries? What proposals for such transfers have been made? Do these proposals represent an application of Keynesianism to the problems of international development and, if so, is this application legitimate?
Keywords: 330; Development Policy